Techniques in surgical navigation of extremity tumors: state of the art - Aponte-Tinao, Luis A. (Curr Rev Musculoskelet Med, 2015)
Image-guided surgical navigation allows the orthopedic oncologist to perform adequate tumor resection based on fused images (CT, MRI, PET). Although surgical navigation was first performed in spine and pelvis, recent reports have described the use of this technique in bone tumors located in the extremities. In long bones, this technique has moved from localization or percutaneous resection of benign tumors to complex bone tumor resections and guided reconstructions (allograft or endoprostheses). In recent years, the reported series have increased from small numbers (5 to 16 patients) to larger ones (up to 130 patients). The purpose of this paper is to review recent reports regarding surgical navigation in the extremities, describing the results obtained with different kind of reconstructions when navigation is used and how the previously described problems were solved.